THE CORRELATION BETWEEN STUDENTS’ INTERNET ACTIVITY FREQUENCY AND THEIR VOCABULARY SIZE AT IAIN BUKITTINGGI - Ramadhan, M. Rizki; Syahrul, Syahrul (Institut Agama Islam Negeri Ponorogo, 2021)
The design of this research was correlational research. This research aimed to find out the correlation between students’ internet activity frequency and their vocabulary size. In this research, the researcher found some problems, such as some students frequently used the internet. However, their vocabulary was still limited, and some students rarely used the internet and had much vocabulary. The researcher used quantitative research. The population in this research was 108 students that were the total of the students in the seventh semester in IAIN Bukittinggi. The researcher took 30% of the population as a sample of this research which was 33 students. The researcher collected the data used questioners and tests. Based on the finding, there was a significant correlation between students”˜ internet activities frequency and their vocabulary size that used SPSS 20. First, It had sig values is smaller than alpha (0,000001<0,05) or r-measured was bigger than r-table 0,730 > 0,3440. Second, there was a positive correlation between both variables (+0.730). Third, the magnitude of the correlation was high, with a score between 0.71- 0.90. The result showed that there is a correlation between student’s internet activity frequency and their vocabulary size.